Mengenali Medical Error dan Optimalisasi Patient Safety di Intensive Care Unit (ICU) - Adiyanto, Bowo; Suwarman (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Characteristics of patients treated in the ICU are patients with critical conditions, acute, with many comorbidities, the number of actions and medications and treatments by multidisciplinary and multi-specialist. This condition is a challenge to be able to develop safety culture in the ICU. The safety culture in the ICU must be aware of and have high vigilance that the potential for medical errors is quite high in the ICU and has a severe impact on patients. Systematic strategies and multifactorial approaches are needed to improve patient safety and reduce medical errors at the ICU. Improving safety culture, ensuring commitment to national patient safety regulations, investing in safe infrastructure, optimizing the role of units in identifying potential errors and standardizing services according to the latest evidence base are the basic factors needed to support safe and quality patient care at ICU . It is important for the next stage to manage and measure the processes and outcomes in the service, and ensure that patients receive optimal therapy in accordance with evidence base practice. In addition to focusing on patient safety areas that have been regulated by national regulations, focus on areas with an appropriate evidence base to be applied in ICU care such as protocol development, checklists, care bundles, simulation-based education, and CUSP programs to optimize the role of units in the program patient safety. The efforts mentioned above to be able to succeed certainly require organization, leadership, multidisciplinary and multi-specialist cooperation, as well as individual service ends who are committed and consistent to the development of safety culture in the ICU.